The grammatical gender of fish generic nomina based on the stem—butis (Teleostei: Perciformes: Gobioidei) - Kottelat, Maurice (Zootaxa, 2011)
The word ‘name’ having various meanings depending on context, in order to avoid confusion and simplify reading I here use the word nomen (plural nomina) to denote 'scientific names'.